STUDY OF THE LONG-TERM EFFECTS OF DIABETES ON THE OVERALL HEALTH AND QUALITY OF LIFE IN THALASSEMIA PATIENTS - Abdulhameed Rashid Hameed ahmed; Rasha Ahmed Abdullah; Maha Saddam wasmi; Rawaa Abd Alkareem Alush; Ammar Abbass Mehsun (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Thalassemia is a genetic blood disorder characterized by chronic anemia, requiring regular blood transfusions and chelation therapy. Diabetes mellitus is a common complication in thalassemia patients, primarily due to iron overload affecting the pancreas. This study investigates the long-term effects of diabetes on the overall health and quality of life in thalassemia patients. The research aims to understand how diabetes exacerbates complications associated with thalassemia and to identify strategies for improved management and care. The study includes a cohort of thalassemia patients with diabetes, compared to a control group of thalassemia patients without diabetes. Parameters assessed include glycemic control, incidence of diabetes-related complications, and overall health markers such as liver function, cardiovascular health, and renal function. Quality of life is measured using standardized questionnaires addressing physical, emotional, and social well-being. Preliminary findings indicate that thalassemia patients with diabetes have a significantly higher incidence of comorbid conditions, including cardiovascular disease and renal impairment (De Sanctis et al., 2016). Additionally, the quality of life in these patients is notably lower, with increased reports of fatigue, pain, and psychological distress (Haines et al., 2013). Effective management of diabetes in thalassemia patients, through regular monitoring and tailored treatment plans, is crucial in mitigating these adverse effects and improving patient outcomes (Farmaki et al., 2006). This study underscores the importance of integrated care approaches for thalassemia patients with diabetes, emphasizing the need for multidisciplinary teams to address the complex interplay of these conditions. Further research is needed to develop targeted interventions that can enhance the long-term health and quality of life for this vulnerable patient population. Results: study indicated that plant extracts exhibited higher inhibition than antibiotics. The minimum inhibitory concentration (MIC) while the results of the lowest inhibitory concentration of carvacrol for the bacterial species under study showed that it had an effect at a concentration of 615 µg/ml against Escherichia coli, 307.5 µg/ml for the species Corynebacterium stratium, Morganella morganii and Pseudomonas aeruginosa, and the least effect was 76.875 µg/ml on Staphylococcus aureus, it gave less results than the antibiotic used Carvacrol (Absorbance was measured at Wavelength 600) .